The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1186/1471-2164-14-104
|View full text |Cite
|
Sign up to set email alerts
|

A highly expressed miR-101 isomiR is a functional silencing small RNA

Abstract: BackgroundMicroRNAs (miRNAs) are short non-coding regulatory RNAs that control gene expression usually producing translational repression and gene silencing. High-throughput sequencing technologies have revealed heterogeneity at length and sequence level for the majority of mature miRNAs (IsomiRs). Most isomiRs can be explained by variability in either Dicer1 or Drosha cleavage during miRNA biogenesis at 5’ or 3’ of the miRNA (trimming variants). Although isomiRs have been described in different tissues and or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 62 publications
(87 reference statements)
10
80
2
Order By: Relevance
“…2A,B). This suggests that these 5-isomiRs represent distinct regulatory entities and is in stark contrast to other reports, which concluded that 5 ′ -isomiRs mostly share their targets (Cloonan et al 2011;Llorens et al 2013).…”
Section: Mir-142-3p 5 ′ -Isomir Expression Is Conserved In Vertebratescontrasting
confidence: 89%
See 1 more Smart Citation
“…2A,B). This suggests that these 5-isomiRs represent distinct regulatory entities and is in stark contrast to other reports, which concluded that 5 ′ -isomiRs mostly share their targets (Cloonan et al 2011;Llorens et al 2013).…”
Section: Mir-142-3p 5 ′ -Isomir Expression Is Conserved In Vertebratescontrasting
confidence: 89%
“…Thus, miR-223 5 ′ -isomiR expression appears to broaden the overall range of miR-223 targets. The prediction that 5 ′ -isomiR expression can impact miRNA target ranges is further supported by the confirmation of small sets of differentially regulated targets for an aberrant miR-307 5 ′ -isomiR in flies (Fukunaga et al 2012) and for transfected 5 ′ -isomiRs of miR-133a, miR-101, and miR-9 (Humphreys et al 2012;Llorens et al 2013;Tan et al 2014). On the other hand, it has been suggested that 5 ′ -isomiRs have highly overlapping targets (Cloonan et al 2011;Llorens et al 2013) and could therefore act redundantly, to increase the effective miRNA dosage or reduce offtarget effects (Cloonan et al 2011).…”
Section: Introductionmentioning
confidence: 83%
“…The sequence variants of the miRNAs termed isomiRs were discovered in recent years (Guo et al, 2012;Li et al, 2012;Llorens et al, 2013). In animals, some of the isomiRs have been demonstrated to have biological roles (Cloonan et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Advanced research from NGS (next-generation sequencing) suggests isomiRs are multiple distinct mature miRNAs that arise from the same hairpin arm and 5' or 3' ends of their sequences and are different from canonical miRNAs in public databases such as miRBase (9). Moreover, recent studies have shown variation in cleavage site for DROSHA and DICER1 enzymes or even other miRNAs processing enzymes or posttranscriptional editing which lead to sequence modification in miRNAs (1) that are classified as "trimming variants" (10). Further evidences have shown there are another group of isomiRs that stem from Argonaute 2(AGO2) cleavage independent of Dicer.…”
Section: Isomir Originmentioning
confidence: 99%